Health risk assessment of heavy metals (Zn, Cu, Cd, Pb, As and Cr) in wheat grain receiving repeated Zn fertilizers. (February 2020) - Liu, Yu-Min; Liu, Dun-Yi; Zhang, Wei; Chen, Xiu-Xiu; Zhao, Qing-Yue; Chen, Xin-Ping; Zou, Chun-Qin
Abstract: Soil application of Zn fertilizer is an effective approach to improve yield and Zn accumulation in wheat grain. However, it remains unclear whether repeated Zn application can result in high accumulation of heavy metals (HMs) in soils and grains and thus represents a potential risk for human consumption. This study aimed to evaluate the health risk assessment of HMs in a wheat production system which had continuously received 8 years of Zn application at varying rates (0, 2.3, 5.7, 11.4, 22.7, 34.1 kg Zn ha −1 ). The results showed that Zn application significantly increased the soil total Zn concentration without affecting concentrations of As, Pb, Cd, Cu and Cr. Across Zn rates, Zn application increased grain concentrations of Zn, Pb and Cd by 75%, 51% and 14%, respectively, and reduced grain As concentration by 14%. The human health risk assessment revealed that the threshold hazard quotients for the individual HM were below 1, independent of Zn rates. The hazard index (HI) values at Zn rates of 11.4, 22.7 and 34.1 kg Zn ha −1 were significantly greater than that at null Zn treatment. Furthermore, exposures to As, Cu and Zn accounted for 97% of HI at all Zn rates. Analysis of the threshold cancer risk with Pb and As showed that ingestion of wheat grain even from highest Zn application rate wouldn't bring the lifetime carcinogenic risk. In contrast, long-term Zn application significantly reduced the carcinogenic risk of As by 9.7–26.5%. In conclusion, repeated soil applications of Zn at optimal rate (5.7 kg Zn ha −1 ) didn't cause health risk for Zn, Cu, Cd, Pb, Cr, and As, while improving productivity and grain Zn concentration of wheat to meet human recruitment. Our study highlights the importance of appropriate Zn fertilizer management in improving grain quality while reducing HMs risks from human consumption. Graphical abstract: Image 1 Highlights: Eight-year Zn application did not cause soil Zn, Cu, Cd, Pb, As and Cr pollution. Repeated 8 years' Zn fertilization at 5.7 kg Zn ha −1 realized Zn biofotification. Application of optimal Zn rate did not bring any addition of non-carcinogenic risk. Application of optimal Zn rate reduced the carcinogenic risk exposed to As. Abstract : Main finding: Zinc application rate at 5.7 kg Zn ha −1 can guarantee grain Zn nutrition for human consumption while preventing any adverse effect of non-carcinogenic and carcinogenic risks.